2018
DOI: 10.31234/osf.io/hkqcs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I Get Knocked Down but I Get Up Again: The Effects of Listening to Music When Sad on Young Adults

Abstract: *THIS PAPER HAS NOT YET BEEN PEER REVIEWED* Listening to music is a strategy many people use to regulate their emotions, especially sadness. However, there is disagreement about whether listening to music is a healthy way to regulate emotions, with some research finding that sad music worsens a sad state, especially for people high in rumination. To further explore the immediate consequences of music listening when sad 128 young adults (41% male, aged 18 to 25 years) were induced into a sad emotional state pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…While distraction is known as one of the most effective strategies for mood repair (Augustine & Hemenover, 2009; Salovey et al, 1999), this finding may seem at odds with the choice of musical pieces with a sadder expression in the comfort condition. However, it has been shown that the engagement with sad excerpts can make listeners feel better (Eerola & Peltola, 2016; Eerola et al, 2016; Larwood & Dingle, 2018; Yoon et al, 2020) and that the mood enhancement might stem from the high aesthetic value of the selected sad music (Garrido & Schubert, 2011b; van den Tol & Edwards, 2014). Thus, choosing music with a sad expression is compatible with mood improvement, supporting the notion that listening to music can support mood repair.…”
Section: Discussionmentioning
confidence: 99%
“…While distraction is known as one of the most effective strategies for mood repair (Augustine & Hemenover, 2009; Salovey et al, 1999), this finding may seem at odds with the choice of musical pieces with a sadder expression in the comfort condition. However, it has been shown that the engagement with sad excerpts can make listeners feel better (Eerola & Peltola, 2016; Eerola et al, 2016; Larwood & Dingle, 2018; Yoon et al, 2020) and that the mood enhancement might stem from the high aesthetic value of the selected sad music (Garrido & Schubert, 2011b; van den Tol & Edwards, 2014). Thus, choosing music with a sad expression is compatible with mood improvement, supporting the notion that listening to music can support mood repair.…”
Section: Discussionmentioning
confidence: 99%
“…A Web-based experiment found listening to self-selected sad music increased depressive moods and listening to happy music reduced them [34]. However, a partial replication of that study found both participant- and experimenter-selected sad music reduced a depressive mood if a negative mood was induced (via a video clip) before music listening [35]. Finally, music use among people who use cognitive reappraisal as an emotion regulation strategy has been found to enhance well-being, whereas the use of expressive suppression reduced well-being [36].…”
Section: Introductionmentioning
confidence: 99%